2013
DOI: 10.5402/2013/471632
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Genetic Linkage Map and QTL Analysis of Sink-Size Traits in Pearl Millet (Pennisetum glaucum)

Abstract: A linkage map, primarily based on SSCP-SNP markers, was constructed using 188 F 2:3 mapping population progenies produced from a cross between two pearl millet inbred lines having diverse parentage. The skeleton linkage map covered 1019 cM and it comprised of 44 markers distributed across the seven linkage groups. Average adjacent-marker intervals ranged from 14 cM on LG1 to 38 cM on LG6, with an overall mean of 23 cM. Using the F 2 linkage map and phenotypic data from the F 2 and F 2:3 generations of the mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…In contrast to previous studies, segregation of almost all LG3 loci in both populations was distorted, which may explain part of the increase in LG3 length. Similar to previous studies reported by Liu et al (1994), Gulia (2004), and Vengadessan (2008), a big inter-marker gap was also detected on LG3 of the (ICMB 841 × 863B)-based population in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to previous studies, segregation of almost all LG3 loci in both populations was distorted, which may explain part of the increase in LG3 length. Similar to previous studies reported by Liu et al (1994), Gulia (2004), and Vengadessan (2008), a big inter-marker gap was also detected on LG3 of the (ICMB 841 × 863B)-based population in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In general, different map lengths reported previously in pearl millet were the result of variation in recombination frequencies of different population structures, numbers of mapped markers, population generation, and population size. Recently Vengadessan (2008) reported the longest SSR-based skeleton linkage map for F 2 -derived F 3 progenies with a length of 1018.7 cM accommodating only 44 well-distributed markers. Gulia (2004) also reported a large map using SSRs with map length of 748 cM for an F 2 population.…”
Section: Discussionmentioning
confidence: 99%
“…In pearl millet improvement, utilization of wild relatives as donors of specific traits such as apomixes (Hanna 1987), or resistance to pests and diseases (Wilson et al 2004) is also scarce. Further, most of the allele mining for agronomically important traits including biotic and abiotic stress resistance has been conducted using bi-parental mapping populations (Yadav et al 2002(Yadav et al , 2004Bidinger et al 2007;Sehgal et al 2012;Vengadessan et al 2013).…”
Section: Potential Of Association Studies For Germplasm Enhancementmentioning
confidence: 99%
“…The relatively large population size (295 RILs from 81B-P13×AIMP92901 deriv-P03) used for construction of the genetic linkage mapspresented here as compared with other studies 16,1,21 , was highly advantageous for further exploitation of these maps. These larger population sizes improvethe estimation of marker orders, which in turn improves the resolution of QTL mapping ofagronomic traits.…”
Section: Linkage Groupmentioning
confidence: 99%